Experimental evidence of the photonic band gap in hybrid one-dimensional photonic crystal based on a mixture of (HMDSO, O2). (August 2016) - Amri, R.; Sahel, S.; Manaa, C.; Bouaziz, L.; Gamra, D.; Lejeune, M.; Clin, M.; Zellama, K.; Bouchriha, H.
Abstract: Hybrid One-dimensional photonic crystal coated from a mixture of an organic compound (HMDSO) and oxygen (O2 ) is elaborated by PECVD technique. The originality of the method consists in obtaining layers of different permittivity with the same gas mixture, but with different flow. The change in flow is optimized to obtain organic/inorganic layers of good quality with high and low refractive index of 2.1 and 1.4 corresponding respectively to HMDSO and SiO2 materials as assigned by IR measurement. Evidence of the photonic band gap is obtained by measuring the transmissions and reflections spectra which show that it appears only after 13 periods with a width of 325 nm corresponding to energy 3.8 eV. We have also introduced a defect in this photonic structure by changing the thickness of central layer, and observed the presence of a frequency mode corresponding to this defect. Our results are interpreted by using a theoretical model based on transfer matrix wich well reproduced the experimental data. Highlights: The (HMDSO, O2 ) films are deposited by PECVD process are found to be appropriate as a new periodic layers. The optical characteristics of the films are controlled by varying the oxygen/HMDSO flow rate ratio. The properties of 1D photonic crystal have been studied experimentally and they are theoretically confirmed.